Computational analysis of water surge phenomenon at power station / Badruzzaman Kamaruzaman - Badruzzaman, Kamaruzaman (2019)
In such confined system for water pipeline, a sudden displacement of flow that causes large pressure destabilize or back pressure is called water hammer. The called is given due to the sound that occurs during the back flow of water. It is most important consideration of many hydraulic design structure due to extreme variation of pressure cause by the pump. The compressibility of water and the elasticity of pipes, pressure waves will then spread in the pipe until they are decreased at certain velocity, which is dependent on the pipe material and wall thickness. Through the effects of the water hammer changing, range from slight changes in pressure and velocity to sufficiently high pressure or vacuum through to failure of fittings, and burst pipes. Figure 1 shows burst mild steel pipe due to water hammer pressure. This pipe thickness and pipe material is not sufficient to sustain the water hammer pressure. Therefore, pipe burst and suitable mathematical modeling of the different ingredient in hydraulic system is necessary to get, useful results, which help fulfill these objectives. In this paper mathematical modeling used to develop computer program to simulate the hydraulic transient in simple pipe. There was no need to consider cases of unsteady flow, either in open channels or in closed pipes and conduits. The action of waves on shore 1ines, in bays and ports, and a1ong canals, was the only prob1em simi1ar to water-hammer known in early times, and the mathematical and physical knowledge in those days was unable to cope with this problem except by construction of breakwaters for protection of harbors and shipping. This branch of hydrau1ics, now designated as coastal engineering, which deals with tida1 and surface waves, has become a very important field, particularly in this 20th century. Because of the rapid flow changes, a pressure wave is propagated while a negative down surge travels down the pipeline to the discharge outlet where it is reflected. The reflected wave will in turn creates a positive surge along the pipeline. Unlike some aspect of the system behavior that are conservative when neglected, this phenomenon cannot be neglected as it increases the severity of water hammer. Column separation is the discontinuity in the water column caused by excessive tension when the pressure is reduced to the vapor pressure of water. Large diameter thin walled pipelines are particularly vulnerable to shell collapse under this condition. On the other case, if the adverse pressure is not acceptable, suitable surge suppression device shall be recommended to limit the pressure to acceptable levels.